2015
DOI: 10.15557/jou.2015.0003
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of findings in clinical and high resolution ultrasonography examinations of the painful shoulder

Abstract: ObjectiveHigh resolution ultrasonography is a non-painful and non-invasive imaging technique which is useful for the assessment of shoulder pain causes, as clinical examination often does not allow an exact diagnosis. The aim of this study was to compare the findings of clinical examination and high resolution ultrasonography in patients presenting with painful shoulder.MethodsNon-interventional observational study of 100 adult patients suffering from unilateral shoulder pain. Exclusion criteria were shoulder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
1
16
0
1
Order By: Relevance
“…In our study, we tried to explore the validity of clinical examination in the detection of US findings. The sensitivity and specificity of the supraspinatus test were 71% and 75% and this was different from Micheroli et al who reported sensitivity of 86% and specificity of 50% and this can be explained by the point that the clinical exam is operator‐dependent, can be misinterpreted from person to person according to clinical experience of the examiner and also the patient response can be misleading to the examiner.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we tried to explore the validity of clinical examination in the detection of US findings. The sensitivity and specificity of the supraspinatus test were 71% and 75% and this was different from Micheroli et al who reported sensitivity of 86% and specificity of 50% and this can be explained by the point that the clinical exam is operator‐dependent, can be misinterpreted from person to person according to clinical experience of the examiner and also the patient response can be misleading to the examiner.…”
Section: Discussionsupporting
confidence: 92%
“…S4 1 ). The Sn and Sp were for each test, respectively: from 0.57 to 0.85 and from 0.49 to 0.72 for the palpation test, (30,47), from 0.47 to 0.83 and from 0.36 to 0.75 for Speed test (47)(48)(49), and from 0.32 to 0.86 and from 0.74 to 0.82 for Yergason's manoeuvre (47)(48)(49). from 0.32 to 0.86 and from 0.78 to 0.88 for Yergason's manoeuvre (37,(47)(48)(49)51) Data from studies assessing Speed test and Yergason's manoeuvre were pooled (Table V, Fig.…”
Section: Hrus Accuracymentioning
confidence: 99%
“…Frequently encountered pathologies in this region are listed in ▶ Table 1. Detailed knowledge of the anatomy of this region and its ultrasound appearance is essential to recognize possible pathologies that correlate with the clinical presentation [1]. The focus of this pictorial essay is to review and discuss the anatomical details of the rotator interval of the shoulder, correlate the anatomy with normal ultrasound images and present selected pathologies.…”
Section: Introductionmentioning
confidence: 99%